Nasal response after exercise in swimmers, runners and handball players - Hancı, Deniz; Altun, Hüseyin; Şahin, Ethem; Aydın, Salih (ENT Updates, 2016)
Objective: The aim of this study was to investigate the effects of different physical activities on nasal response. Methods: Young non-professional university teams (male, 20 to 24 years old) were enrolled in this study. Nasal functions were measured with an active anterior rhinomanometry and the saccharine transport method (nasal transport times, NTT) before and immediately after the exercise. After the initial measurements, the first group swam 30 minutes in the swimming pool. The second group (outdoor runners) ran 10 kilometers in approximately 30 minutes. The third group played handball for 30 minutes. The initial findings were compared statistically with the data obtained after exercise. Results: When the reductions in nasal resistance were compared before and after exercise, the inspiration and expiration values of all groups were statistically significant. These three groups were similar regarding the comparison of nasal resistance change percentages. When the NTTs were compared before and after exercise, the decreases in the amount of time were statistically significant in all these three groups after exercise. When the change percentages of the decrease in nasal transport time were compared, the decrease in handball players was statistically significant compared to runners. Conclusion: Nasal resistance reductions and the decreases in NTT were not affected by the type of sports being played or the air quality of the environment.